1996
DOI: 10.1007/bf00194536
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I clinical study of the antipurine antifolate lometrexol (DDATHF) given with oral folic acid

Abstract: Lometrexol is an antifolate which inhibits glycinamide ribonucleotide formyltransferase (GARFT), an enzyme essential for de novo purine synthesis. Extensive experimental and limited clinical data have shown that lometrexol has activity against tumours which are refractory to other drugs, notably methotrexate. However, the initial clinical development of lometrexol was curtailed because of severe and cumulative antiproliferative toxicities. Preclinical murine studies demonstrated that the toxicity of lometrexol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In fact, toxicity has been a more common reason for discontinuation of MTX than poor efficacy (43). Some folate antagonists with a high affinity for FR-␤ are in phase I or phase II trials for the treatment of cancer (44,45). In conclusion, the present findings strongly suggest a role for FR-␤ in the transport of folic acid and folate derivatives in RA SMC and imply that folic acid antagonists with a high affinity for FR-␤ may be useful in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, toxicity has been a more common reason for discontinuation of MTX than poor efficacy (43). Some folate antagonists with a high affinity for FR-␤ are in phase I or phase II trials for the treatment of cancer (44,45). In conclusion, the present findings strongly suggest a role for FR-␤ in the transport of folic acid and folate derivatives in RA SMC and imply that folic acid antagonists with a high affinity for FR-␤ may be useful in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical (21) and clinical therapeutic trials (22,24) 3 have shown that the toxicity of (6R)-DDATHF to animals and man can be substantially decreased by the co-administration of oral folic acid. Animal studies have shown that the toxicity of (6R)-DDATHF can be shifted by a surprising 1000-fold by the administration of rather small doses of oral folic acid to animals on a low folate diet (21).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience and nonclinical studies with methotrexate and lometrexol indicated that severe toxicity may be associated with nutritional folate status (Morgan et al, 1990;Alati et al, 1996;Mendelsohn et al, 1996). In fact, in the study of lometrexol, a significant effect of folate supplementation on toxicity was observed (Laohavinij et al, 1996). Based on these experiences, Niyikiza et al (2002a) investigated relationships between toxicity and baseline patient characteristics for early pemetrexed studies.…”
Section: Pemetrexed (Ly231514 Alimtamentioning
confidence: 99%